A Review on the Roles of Extracellular Polymeric Substances (EPSs) in Wastewater Treatment: Source, Mechanism Study, Bioproducts, Limitations, and Future Challenges - Hasan, Hassimi Abu; Rahim, Nurul Farhana Mohd; Alias, Jahira; Ahmad, Jamilah; Said, Nor Sakinah Mohd; Ramli, Nur Nadhirah; Buhari, Junaidah; Abdullah, Siti Rozaimah Sheikh; Othman, Ahmad Razi; Jusoh, Hajjar Hartini Wan; Juahir, Hafizan; Kurniawan, Setyo Budi (Water (Basel), 2024)
Biological treatment is currently a favorable option to treat wastewater due to its environmentally friendly methods and minimal toxic by-products. The majority of biological wastewater treatment uses bacteria as treatment agents, which are known to have excellent capabilities for removing various pollutants. Researchers have extensively explored the use of extracellular polymeric substances (EPSs) generated by bacteria in wastewater treatment. This review focuses on the sources of EPSs, factors influencing their production, and their role in wastewater treatment. Bacterial species, nutrient availability, pH, temperatures, and the presence of toxins were mentioned to be the factors influencing EPS production by bacteria in wastewater treatment. Produced EPSs by bacteria may promote the aggregation, adsorption, decolorization, and degradation of pollutants. This review highlights the challenges of discovering new potential bacterial species and complex EPS extraction methods, as well as the importance of mass production for larger-scale applications.